Terrestrial temperature evolution of southern Africa during the late Pleistocene and Holocene: Evidence from the Mfabeni Peatland. (1st January 2023) - Fietz, Susanne; Baker, Andrea; Miller, Charlotte S.; Naafs, B. David A.; Peterse, Francien; Finch, Jemma; Humphries, Marc; Schefuß, Enno; Roychoudhury, Alakendra N.; Routh, Joyanto
Abstract: The scarcity of suitable high-resolution archives, such as ancient natural lakes, that span beyond the Holocene, hinders long-term late Quaternary temperature reconstructions in southern Africa. Here we target two cores from Mfabeni Peatland, one of the few long continuous terrestrial archives in South Africa that reaches into the Pleistocene, to generate a composite temperature record spanning the last ∼43 kyr. The Mfabeni Peatland has previously been proven suitable for temperature and hydrological reconstructions based on pollen and geochemical proxies. Here we use branched glycerol dialkyl glycerol tetraethers (brGDGTs) preserved in the Mfabeni peatland to derive a new quantitative air temperature record for south-east Africa. Our temperature record generally follows global trends in temperature and atmospheric CO2 concentrations, but is decoupled at times. Annual air temperatures during Marine Isotope Stage (MIS) 3 were moderately high ( c. 20.5 °C), but dropped by c. 5 °C during the Last Glacial Maximum, reaching a minimum at c. 16–15 ka. Asynchronous with local insolation, this cooling may have resulted from reduced sea surface temperatures linked to a northward shift in the Southern Hemisphere westerly winds. Concurrent with the southward retreat of the westerlies, and increasing sea surface temperatures offshore, warming from minimum temperatures ( c . 15.0 °C) to average Holocene temperatures ( c. 20.0 °C) occurred across the deglaciation. This warming was briefly but prominently interrupted by a millennial-scale cooling event of c. 3 °C at c. 2.4 ka, concurrent with a sudden change in hydrological conditions. The average Holocene temperatures of c. 20.0 °C were similar to those reconstructed for MIS 3, but after the 2.4 ka cooling period, air temperatures in the Mfabeni peat recovered and steadily increased towards the present. In summary, our record demonstrates that land temperature in eastern South Africa is highly sensitive to global drivers as well as nearby sea surface temperatures. Highlights: Peatland brGDGTs provide new quantitative air temperature record for south-east Africa. Last 43 ka do not indicate a clear control of local temperatures by greenhouse gas concentrations and insolation. Mfabeni MAATs are affected, next to global changes, by Indian Ocean SSTs and position of the westerlies. Record underlines sensitivity and vulnerability of south-east Africa to global and regional climate forcings.